‘Alāqat Ḥarakat Nashr al-Islām wa al-Tarbīyah al-Islāmiyyah fī Ṣultanah Aceh - Rosatria, Eri (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
The emergence of such great 'ulama' in the Sultanate of Aceh, north of Sumatra, as Hamzah Fansuri (Hamzah al-Fansuri), Syamsuddin Sumatrani (Shams al-Din al-Sumatrani), Nuruddin Arraniri (Nur al-Din al-Raniri) and Abdurrauf Singkel ('Abd al-Rauf al-Sinkili) could lead one to pose an important questions. Why they emerged in the Sultanate of Aceh and not in other part of Nusantara. This study argues that that their emergence had closely to do with the fact that activity of Islamic learning was strongly supported by the Acehnese sultans.DOI: 10.15408/sdi.v3i1.815